MEANING AS A SOUND – PARAMETER IN LUIGI NONO’S WORK: A DIALECTICS OF ‘PHONETIC – SEMANTIC STRUCTURE’ - Fabien SAN MARTIN (Studia Universitatis Babeş-Bolyai. Musica)
In their text-music relationship, Luigi Nono’s compositions, as early as the late 1950s, integrate words as a full-fledged sound parameter, in their capacity as sounds laden with sense and according to a gradual variety from the pure phoneme to the pure moneme to ambivalent formants. In the light of the theory developed by the Venetian composer in his 1960 lecture ‘Text-Music-Singing’, and of some writings by Jacques Derrida with which this paper comes in resonance, the present study attempts to demonstrate the particular status of words in Luigi Nono’s vocal music, and the precise use of their senses as a sound parameter in itself, through the analysis of the Cori di Didone and the Fabbrica illuminata.